Implementing teacher-centered robotics activities in science lessons: The effect on motivation, satisfaction and science skills - Ozan Coşkunserçe (Journal of Pedagogical Research, 2021)
In studies on the use of robotic in science education, students are generally expected to design and program robots in specially designed robotic laboratories and during extracurricular activities. Although researchers claim that the student-centered approach and active student participation is more effective, teachers generally have to apply traditional teaching strategies in the field of science education due to the high number of students, a lack of materials, insufficient time and lack of professional teaching skills. Robotics activities can be performed in a traditional classroom environment and within a teacher-centered lesson structure. The aim of this study was to investigate the effect of teacher-centered robotics activities performed in science lessons on students' motivation, to determine their satisfaction with the activities and to collect their opinions about the activities. A parallel mixed-methods design was used for data collection. The results of the study indicated that teacher-centered robotics activities increased the motivation of students to participate in science lessons. Moreover, when the interviews with the students were examined, all of them commented that engaging in robotics activities improved their science skills. In addition, the majority of students were satisfied with the robotics activities and had positive feelings about them, believing that they helped them to learn and were enjoyable and interesting.